(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Pd/SiO_2 organic-inorganic hybrid material was prepared by sol-gel method, in which PdCl_2 was added into methyl-modified silica sol. The Pd/SiO_2 sol particle size distribution, the hydrophobicity and phase changes of Pd/SiO_2 hybrid materials calcined at 200, 350, 500, 600 and 750 °C in air atmosphere were discussed. The Pd/SiO_2 sol system exhibits moderate dispersion and the mean particle size of Pd/SiO_2 sol is 2.70 nm. When the calcination temperature is raised to 350 °C, metallic palladium of high crystallinity is formed in the Pd/SiO_2 sample. PdO occurs in minor quantities in the Pd/SiO_2 sample calcined at 500 °C, which increases in amount in the samples calcined at 600 and 750 °C. With the increase of calcination temperature, the Si-CH_3 and Si-OH bands in Pd/SiO_2 materials are found to decrease in absorption intensity and the hydrophobicity on Pd/SiO_2 film surfaces increases. The water contact angle on the Pd/SiO_2 film surface achieves the maximum value as the calcination temperature is up to 350 °C and the particle sizes of the formed metallic Pd are about 15 ∼ 20 nm. The optimal calcination temperature for hydrophobic Pd/SiO_2 membrane materials is about 350 °C.